Lyme Disease in Hispanics in Long Island, New York: A New Health Disparity in the U.S. (4th October 2017) - Khoo, Teresa; Spallone, Amy; Lier, Audun; Abul, Yasin; Wellins, Anna-Marie; Weinbaum, Fredric; Luft, Benjamin; Marcos, Luis A
Abstract: Background: Lyme disease (LD) is the most commonly reported vector-borne illness in the U.S. A risk factor for acquiring LD is the exposure to outdoors. In Long Island, Hispanics compromise a large share of the outdoor occupational workforce. Methods: A retrospective chart review was performed in all patients with ICD-9 or ICD-10 diagnostic codes for LD between 2011–2016 in SHH and 2010–2015 in SBUH. Inclusion criteria was defined as a clinical scenario compatible with LD (erythema migrans -EM, arthritis, central nervous system (CNS) involvement, carditis, meningitis) and serological confirmation by western blot according to CDC (SBUH) or Imugen® (SHH) criteria. Results: Out of 1, 026 cases (766 SBUH;260 SHH) that carried a diagnosis of LD, 284 cases (22% Hispanics) met inclusion criteria and were added to final analysis (241 SBUH: 43 SHH). The mean age was 48.8 (SD:17.8) and 48.3 (SD:17.5) years-old in H and NH, respectively (p > 0.05). Most were male (H:62.2%; NH: 54.3%; P = 0.2). In the univariate analysis, headaches were more frequently present in H (42.6%) than in NH (26.6%) ( P = 0.015). In the logistic regression analysis, the following symptoms were significantly different between H and NH: headaches (OR 1.17, 96% CI 1.60–6.59, P = 0.001) and peripheral neuropathy (OR 0.38, 95% CI: 0.15-0.96, P = 0.04). Among seasons, H were more frequently diagnosed with Lyme during spring months than NH (H: 26.3% vs. NH: 12.6%, P = 0.03) Conclusion: Hispanics have a greater risk for presenting with headaches and less peripheral neuropathy than NH. Initiation of outdoor work among H may be the reason of this disproportionate presentation of LD symptoms during spring months. These findings may suggest the propensity for Hispanics to go underdiagnosed with LD, despite their high likelihood of exposure through their occupations in this region. Disclosures: All authors: No reported disclosures.